Penegakan Hukum Kejahatan Carding dengan Modus Wiretapping di Polda Jawa Timur - Miftachul Nurjanah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Modernization in the field of financial transactions is the modernization of new criminal modes, this can occur because the electronic financial transaction network system creates a blemish that can be exploited by every cyber crime actor. In this case, it is the carding perpetrator, the carding crime has also undergone a revolution in accordance with the development of the financial transaction system, of course in this era of electronic banking, the crime of carding also uses the internet network system. Wiretapping is done by tapping credit card transactions through a communication network. there are problems faced in law enforcement of Carding wiretapping crime. In this case, the author is interested in exploring more clearly related to how the cyber crime unit of the East Java Police in carrying out law enforcement for carding crimes. This study uses a normative juridical approach, in order to examine legal protection for victims of carding crime, so that later it produces a descriptive conclusion. The implementation of law enforcement is carried out by means of members of the Cyber Team of the Ditreskrimsus Polda Jatim conducting investigations in the form of cyber patrol activities against perpetrators who previously communicated on social media such as Facebook groups by using wiretapping tools that can find perpetrators quickly through the Cyber system. The efforts that have been made by the Cybercrime Unit of the East Java Regional Police are to create a report hotline number addressed to the public to make it easier to submit complaints. And we also make socialization through social media that never give personal data to others.